Pension security in the global economy: markets and national institutions in the 21st century - Clark, G (Pion Ltd., 2003)
This paper begins with the issue of pension security, referencing the desired predictability, stability, long-lived nature of benefits, and coverage of retirement incomes. Also considered is the issue of pension security in the light of global financial market performance and integration. Having discussed issues of nation-state fiscal capacity and the consequences of the technology, media, and telecommunications speculative bubble for stock market returns it is suggested that pension security is also a matter of institutional integrity. This is illustrated with reference to debate in US Congress over the proper response to the Enron debacle. It is argued that no public or private institutions (including the nation-state and large corporations) can now guarantee the final value of pension benefits. As the baby boom generation comes to retirement across the Western world, pension security in the form of guaranteed pension benefit value is a hollow ideal; a chimera on the horizon of nation-state politics that cannot be sustained, notwithstanding the commitment of many to social justice and social solidarity between the generations.